METHODS OF RESOLUTION OF LABOR DISPUTES: NEW TRENDS (Archive of Conferences, 2021)
The article describes the work being done to introduce modern mechanisms for resolvingdisputes in the field of labor law. Also, other (alternative) methods of resolving labor disputes havebeen analyzed on the basis of research conducted by the International Labor Organization's ResearchCenter and the experience of developed countries.